PENGARUH DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, PENDAPATAN ASLI DAERAH, DAN PENDAPATAN DOMESTIK REGIONAL BRUTO TERHADAP BELANJA MODAL (Studi Empiris Pada Pemerintah Daerah Kabupaten / Kota Se Jawa Tengah) (Students' Journal of Accounting and Banking, 2014)
This study aims to test the Influence of DAU, DAK, revenue and GDP against Capital Expenditure Empirical Study On Local Government / City Se Central Java. capital expenditure has not been fully implemented for the growth of public welfare, especially for the management of regional shopping capital expenditure is still not oriented to the public. One of them caused by the management of the shopping collide with the interests of sheer class. The sample used in this study is the financial data of local government district / municipality in the province of Central Java in 2010 to 2012 the data collection method used in this study unsaturated sampling where all populations are used as samples in this study. The analytical tool used is multiple linear regression t test, f test, and test the coefficient of determination. The results of this study indicate that the general allocation fund variables significant negative effect on capital expenditures. Special allocation variables significant negative effect on capital expenditures. Revenue variables significant negative effect on capital expenditures. gross regional domestic product variables significant positive effect on capital expenditures. Keywords: Capital Expenditure, allocation of General Fund, Special Revenue Fund allocations Local, regional gross domestic product